Prevalence and factors associated with Mycobacteremia and mortality among febrile HIV infected patients in Mwanza, Tanzania - Paulina Manyiri; Rodrick Kabangila; Christa Kasang; Martha F. Mushi; Mariam M. Mirambo; Stephen E. Mshana (International Journal of Infectious Diseases, 2018)
Objectives: This study investigated the prevalence and factors associated with mycobacteremia and mortality among febrile HIV infected patients in developing countries. Methods: A hospital based cross-sectional study was conducted among febrile HIV patients admitted at Bugando Medical centre and Sekou Toure hospital between November 2016 and March 2017. Blood culture was done on BACTEC Myco/F Lytic bottles. Clinical and demographic data were collected using a pre-tested data collection tool. Results: A total of 154 patients with the mean age of 41.5 ± 12.2 were enrolled. Females formed the majority, 93 (60%) of the study participants. The prevalence of Mycobacteremia was 3.3% while that of other bacteria was 8.4%. Age (p = 0.03), recent HIV diagnosis (p = 0.005), not taking HAART (p = 0.031) and low CD4+ count (p = 0.002) were significantly associated with Mycobacteremia. Factors significantly associated with 14-day in-hospital mortality were advanced HIV infection (p < 0.001), poor ART adherence (p < 0.001), low CD4+ (p = 0.0002) and Mycobacteremia (p = 0.007). Conclusion: The prevalence of Mycobacteremia was low; however, it was significantly associated with mortality. Mycobacteremia should be suspected in high risk febrile HIV infected individuals followed by early appropriate treatment in order to reduce associated morbidity and mortality. Keywords: Mycobacteremia, Mortality, Fever, HIV